Over a million students use our free study notes to help them with their homework
Example solve the following, equation 1: x2+2y=9 equation 2: y=x+3In this example we have to use substitution, therefore we sub in equation 2 into 1 to get the following x2+2(x+3)=9 ...
2^6 = 64 (2x2x2x2x2x2)6^2= 36 (6x6) 64+36= 100Square root of 100= 10 (10x10=100)
8/50 = 16/10016%
a^2 + b^2 = c^2c^2 = 8^2 + 6^2c^2 = 64 + 36c^2 = 100c=10
By putting u=cosx and v’= e^x , use the by parts formula to get:∫e^(x)(cos(x)) dx = cos(x)e^x - ∫-(e^x)sin(x) dx. Use by parts again on the second term to get ∫ =cos(x)e^x + sin(x)e^x - ∫e^(x)(c...
←
663
664
665
666
667
→
Internet Safety
Payment Security
Cyber
Essentials